A retrospective cohort review of intrahepatic cholestasis of pregnancy in a South Australian population. (November 2017) - Marathe, Jessica A; Lim, Wei How; Metz, Michael P; Scheil, Wendy; Dekker, Gustaaf A; Hague, William M
Abstract: Objective: : To review the management and outcomes of Intrahepatic Cholestasis of Pregnancy (ICP) in South Australia (SA) over the past decade. Design: : Retrospective cohort review. Setting: : Public clinics at two teaching hospitals in SA. Population: : All pregnancies associated with ICP (defined as pruritus with serum bile acids ≥ 10 μmol/L) managed 2001–2010. Methods: : Identification of subjects (laboratory database), detailed chart-review to ascertain demographics, maternal/perinatal outcomes and associated pregnancy comorbidities, analysis of mild/severe disease cohorts, comparison with normal population data, using Student's t -test or Mann-Whitney U test as appropriate for continuous variables, and Pearson's chi-square test or Fisher's exact test for categorical variables. Unadjusted odds ratios (OR) with 95% confidence intervals (95% CI) were calculated in comparison with the general pregnant population for clinically significant outcomes. Results: : 320 women (359 pregnancies) were diagnosed with ICP over the 10-years: incidence 0.6%/year. Within the cohort, the incidences of gestational diabetes (12.5%; OR 3.06, 95% CI 2.23–4.18), pre-eclampsia (10.3%; OR 75.84, 95% CI 52.91–178.70), and spontaneous preterm labour (23.1%; OR 2.05, 95% CI 1.41–2.98) were much higher than in the general SA pregnant population. Pregnancies with severe ICP (serum bile acids ≥ 40 μmol/L) had ICP diagnosed earlier (231 vs 248 days, P < 0.001), and ended earlier (256 vs 260 days, P < 0.001) with lower birthweights (2827 g vs 3093 g, P < 0.001) than those with mild ICP. Neonates of severe ICP mothers were more likely to require special-care-nursery admission, but perinatal complication rates did not differ. There were no stillbirths. Conclusion: : This large Australian retrospective cohort study confirms generally favourable outcomes associated with ICP, mild or severe, with no stillbirths, likely secondary to proactive medical management. A high proportion of pregnancies were also affected by gestational diabetes, pre-eclampsia, and/or spontaneous pre-term labour compared with the general population.